Plant Virology Protocols From Viral Sequence to Protein Function - Foster, Gary.; Johansen, Elisabeth; Hong, Yiguo; Nagy, Peter; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2008)
Following the considerable success of the first edition of Plant Virology Protocols, this exciting new edition covers the many new techniques that are now applied to the examination and understanding of plant viruses. Each section of Plant Virology Protocols, Second Edition presents the most novel methods and protocols to allow researchers more effective approaches to study plant viruses. The many subjects covered in this important new edition range from techniques for investigating viral nucleic acid sequence, protein analysis and investigation of protein function, techniques for microscopy/GFP visualization and analysis/protein tagging/generation of infectious clones and other such tools, as well as areas of genomics and interactions with host factors and plant-based studies. Plant Virology Protocols, Second Edition: From viral sequence to protein function is indispensable to laboratory investigators studying plant viruses.
General Introduction -- Plant–Virus Interactions -- Role of Capsid Proteins -- Role of Plant Virus Movement Proteins -- Multiple Roles of Viral Replication Proteins in Plant RNA Virus Replication -- Role of Silencing Suppressor Proteins -- Role of Vector-Transmission Proteins -- Viral Nucleic Acid Sequence/Function Analysis -- In Vivo Analyses of Viral RNA Translation -- In Vitro Analysis of Translation Enhancers -- Identification of Plant Virus IRES -- Analysis of Geminivirus DNA Replication by 2-D Gel -- Begomoviruses: Molecular Cloning and Identification of Replication Origin -- Analysis of Viroid Replication -- Biochemical Analyses of the Interactions Between Viral Polymerases and RNAs -- In Situ Detection of Plant Viruses and Virus-Specific Products -- Detection of siRNAs and miRNAs -- Cloning of Short Interfering RNAs from Virus-Infected Plants -- Solution Structure Probing of RNA Structures -- RNA Encapsidation Assay -- Protein Analysis and Investigation of Protein Function -- Surface Plasmon Resonance Analysis of Interactions Between Replicase Proteins of Tomato Bushy Stunt Virus -- Biochemical Approaches for Characterizing RNA–Protein Complexes in Preparation for High Resolution Structure Analysis -- Probing Interactions Between Plant Virus Movement Proteins and Nucleic Acids -- Movement Profiles: A Tool for Quantitative Analysis of Cell-to-Cell Movement of Plant Viral Movement Proteins -- Analysis of siRNA-Suppressor of Gene Silencing Interactions -- Phosphorylation Analysis of Plant Viral Proteins -- Analysis of Interactions Between Viral Replicase Proteins and Plant Intracellular Membranes -- Membrane and Protein Dynamics in Virus-Infected Plant Cells -- Site-Directed Mutagenesis of Whole Viral Genomes -- Viral Protein–Nucleic Acid Interaction: South (North)-Western Blot -- Protein–Protein Interactions: The Yeast Two-Hybrid System -- NMR Analysis of Viral Protein Structures -- Localization of Viral Proteins in Plant Cells: Protein Tagging -- Microscopy/GFP/Protein Tagging/Infections Clones and Other Such Tools -- Construction of Infectious Clones for RNA Viruses: TMV -- Construction of Infectious cDNA Clones for RNA Viruses: Turnip Crinkle Virus -- Construction of Infectious Clones for DNA Viruses: Mastreviruses -- Construction of Infectious Clones of Double-Stranded DNA Viruses of Plants Using Citrus Yellow Mosaic Virus as an Example -- Insertion of Introns: A Strategy to Facilitate Assembly of Infectious Full Length Clones -- Analysis of Cell-to-Cell and Long-Distance Movement of Apple Latent Spherical Virus in Infected Plants Using Green, Cyan, and Yellow Fluorescent Proteins -- Agroinoculation: A Simple Procedure for Systemic Infection of Plants with Viruses -- Geminivirus: Biolistic Inoculation and Molecular Diagnosis -- Genomics, Host Factors and Plant Based Studies -- Expression Microarrays in Plant-Virus Interaction -- Genome-Wide Screens for Identification of Host Factors in Viral Replication -- Phosphorylation of Movement Proteins by the Plasmodesmal-Associated Protein Kinase -- Virus-Induced Gene Silencing as a Tool to Identify Host Genes Affecting Viral Pathogenicity -- Yeast Two-Hybrid Assay to Identify Host–Virus Interactions.
Keywords: Plant science; Botany; Virology; Plant genetics; Plant Sciences; Virology; Plant Genetics and Genomics